Visy, kity, abū. Is the lengthening of the word ending typical of all Vilnius residents? - Čičirkaitė, Ramunė (Taikomoji kalbotyra, 2018)
The current article analyzes the variability of length of /i/ and /u/ in stressed word endings characteristic to Lithuanian residents of Vilnius. Some Vilnius residents of Lithuanian origin pronounce these vowels as long or semi-long, though in written language they are written as short vowels. In the Lithuanian standardization ideology, such variability is characterized negatively and is referred to as the lengthening of the word ending. It is socially stigmatized, associated with the speech of uneducated Vilnius residents, speakers that belong to the working class, have a lower social status, or are affected by a Slavic language. The main goal of this survey was to identify the length of the stressed /i/ and /u/ in word endings and to determine with which social categories their longer variants correlate in Vilnius speech. A computerized sound analysis programme was applied to study 800 variants of /i/ and /u/ vowels, which were selected from interviews with 40 Vilnius city dwellers of different age, gender, professional activity, and social status. The analysis has revealed that in the Lithuanian speaking community of Vilnius the length of stressed vowels in word endings functions as a marker of speaker’s age, professional activity, and educational background. A statistically significant higher average length of /i/ and /u/ is typical of those Vilnius residents who are older, educated, and work in traditional industries or manufacturing, but not for service providers.